Electrical, Luminescent and Structural Properties of Nanopillar GaN/InGaN Multi-Quantum-Well Structures Prepared by Dry Etching. (1st January 2016) - Polyakov, A. Y.; Cho, Han-Su; Yun, Jin-Hyeon; Lee, In-Hwan; Yakimov, E. B.; Smirnov, N. B.; Shcherbachev, K. D.
Abstract : GaN/InGaN multiple quantum well (MQW) structures with undoped n-GaN cap imitating true light emitting diodes were grown on sapphire and converted to deep nanopillar (NP) structures by dry etching beyond the MQW region. Structural measurements, electrical measurements on Schottky diodes, microcathodoluminescence (MCL) spectra measurements indicate a strong relaxation of strain in NP MQWs manifested in the prominent increase of the bowing radius of the structures and in the blueshift of the MQW peak in MCL spectra. Various treatments of the as-etched NP MQWs (annealing at 700°C, etching in KOH, and soaking in (NH4 )2 S) progressively decreased the leakage current of Schottky diodes and increased the MQW MCL peak intensity due to the suppression of the dry-etching damage of the nanopillar sidewalls.